(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rinawati DY, Reflinur, Dinarti D, Sudarsono. 2021. Genetic diversity of sugar palm (Arenga pinnata) derived from nine regions in Indonesia based on SSR markers. Biodiversitas 22: 3749-3755. Sugar palm (Arenga pinnata (Wurmb) Merr.) has an important economic and conservation value. Indonesia has genetic diversity potential of sugar palm, considering the widespread distribution of sugar palm in Indonesia which has variations in geographical type. This study aims to determine the diversity and relationship of sugar palm from nine regions in Indonesia based on SSR markers. The genetic material consists of 141 sugar palm accessions derived from Bangka, Lampung, Lebak, Bogor, Tasikmalaya, Brebes, Gowa, Bombana, and Muna. Nine pairs of SSR primers were used for genotyping. The highest and lowest genetic diversity was found in the Bangka and Muna populations, respectively. The genetic diversity within a population (79%) was higher than the genetic diversity between populations (21%). The genetic distance between Bangka and Lebak is the closest (0.033), while between Lampung and Muna is the farthest (0.283). The accession relationship is divided into three major clusters. Clusters 1 consisted of Bangka, Lampung, Bogor, Tasikmalaya, Brebes, Gowa, Bombana and Muna accessions. Cluster 2 consisted of Bangka, Lampung, Lebak, Bogor, Tasikmalaya, Brebes, and Gowa accessions. Cluster 3 consisted of Bangka, Lebak, Brebes, Tasikmalaya, and Gowa accessions. Accession clustering does not show a typical relationship pattern based on geographic location.